Introdução á educação ambiental nas escolas de ensino fundamental I - Lustoza, Cícera Alves (2015)
This work was subject to Environmental Education in Primary Education Schools, the theme was chosen because of growing concern about the changes that man has made and makes the environment. Given the problems that are eliminating life on the planet and endangering the future of the human species, it is necessary to increase the discussions and studies related to the subject, looking for ways to develop a society that is able to live in harmony with what nature offers, without damaging it. This paper aims to discuss what's Environmental Education (EE) and its importance in the formation of conscious and critical citizens, able to intervene in the middle in a sustainable manner, so EE It is in charge of transforming human behavior, not just point out the environmental problems facing the Earth, derived from the human action. The methodology used to carry out the above work was theoretical research and field research conducted in 02 (two) schools municipal city Goioerê-PR. This spatial area, we could see how Environmental Education is being pursued and apprehended by children It was observed that environmental conservation theory is implemented in the knowledge and generating gradually changing habits. The teachers spread the concepts and seek to deploy new way of seeing nature causing behaviors and attitudes will maintain the appropriate environment however , formal education need to work together with government and private agents to effectively there is a significant change in human acts.